Community Understanding of the Pawn Agreement for Village Products in the Rumahkay of West Seram - Berlianty, Teng; Akyuwen, Rory Jeff; Hetharie, Yosia (Jurnal Abdimas, 2023)
The PKM activity with the title " Community Understanding of the Pawn Agreement for Village Products in the West Part of Rumahkay Seram " aims to: (1). Implementing the results of previous research with problems regarding the implementation of hamlet pawn agreements in Laimu Country, Central Maluku and the legal consequences, (2). As a form of education and increasing legal understanding, especially in the field of contracts (agreements) for the people of Rumahkay Country, West Seram Regency . This PKM uses an implementation method in the form of legal education activities carried out in a panel by the presenters, which is then followed by question and answer activities between the community and the presenters. In implementing PKM activities, it was found that the system of pawning hamlet products in Rumahkay Country was carried out in the form of an oral agreement based on trust. This often leads to legal problems because one party can deny the agreement on the grounds that there is no evidence. Therefore, it is recommended to the people of Rumahkay Country to be able to implement a system of pawning village products in the form of a written agreement to avoid various legal problems in the future in the form of default by other parties.